Citrinin against breast cancer: A cytogenotoxicological study - de Oliveira Filho, José Williams Gomes (2020)
Breast cancer is one of the most lethal types of cancer and a leading cause of mortality among Women worldwide. Citrinin (CIT), a polyketide extracted from the fungus Penicillium citrinum, exhibits a wide range of biological activities such as antibacterial, antifungal, and cytotoxic effects. The aim of the current study was to evaluate the antitumoral effects of CIT against 7,12-dimethylbenzanthracene (DMBA)-induced mammary carcinoma in Swiss mice For this, CIT, DMBA and the standard cyclophosphamide (CPA) induced behavioral changes in experimental animals, and these changes were screened by using the rota rod and open field tests. Additionally, hematological, biochemical, immuno-histochemical, and histopathological analyses were carried out. Results suggest that CIT did not alter behavioral, hematological, and biochemical parameters in mice. DMBA induced invasive mammary carcinoma and showed genotoxic effects in the breasts, bone marrow, lymphocytes, and hepatic cells. It also caused mutagenic effects in the formation of micronuclei, bridges, shoots, and binucleate cells in bone marrow and liver. CIT and CPA genotoxic effects were observed after 3 weeks of therapy, where CIT exhibited a repair capacity and induced significant apoptotic damage in mouse lymphocytes. In conclusion, CIT showed antitumoral effects in Swiss mice, possibly through induction of apoptosis.